Effects of RF field rectification and accelerated electron beam generation in the torsatron U-3M during plasma production - Berezhnyj, V.L.; Berezhnaya, I.V.; Voitsenya, V.S.; Pinos, I.B.; Filippov, V.V. (Вопросы атомной науки и техники, 2011)
The presented experimental results show that during the interaction between the RF field and a spatial charge of positive ions having the nonlinear volt-ampere characteristic a part of the RF field is rectified into the direct component. This direct electric field accelerates the electrons emitting from the antenna surface.